2019
DOI: 10.1111/crj.13001
|View full text |Cite
|
Sign up to set email alerts
|

The predictive value of plasma osmolality for in‐hospital mortality in patients with acute pulmonary embolism

Abstract: Introduction and Objectives Prior studies demonstrated that plasma osmolality may have a predictive value for in‐hospital mortality in patients with heart failure and acute coronary syndrome. In addition, plasma glucose and blood urea nitrogen (BUN) levels, the components of plasma osmolality, have been shown to be an important contributor for in‐hospital mortality in acute pulmonary embolism (APE) patients. Hence, the objective of the current study is to evaluate the effect of plasma osmolality upon admission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 22 publications
1
13
0
2
Order By: Relevance
“…Instead, since medium- and long-term follow-up mortality is mainly driven by comorbidities, CCI represent the most appropriate predictor of death, whith sPESI losing its prognostic value. These data are in keeping with other studies' results which found that in PE patients mortality was associated with variables not strictly related to the acute index event, such as plasma osmolality and nutritional indexes [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 92%
“…Instead, since medium- and long-term follow-up mortality is mainly driven by comorbidities, CCI represent the most appropriate predictor of death, whith sPESI losing its prognostic value. These data are in keeping with other studies' results which found that in PE patients mortality was associated with variables not strictly related to the acute index event, such as plasma osmolality and nutritional indexes [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 92%
“…Данные показатели могут рассматриваться как фактор высокого риска тромботических осложнений у данной категории пациентов [13]. Повышение осмолярности плазмы у пациентов с ТЭЛА можно рассматривать как предиктор госпитальной смертности [14].…”
Section: рисунок 2 -зависимость относительного содержания моноцитов оunclassified
“…Данные показатели могут рассматриваться как фактор высокого риска тромботических осложнений у данной категории пациентов [13]. Повышение осмолярности плазмы у пациентов с ТЭЛА можно рассматривать как предиктор госпитальной смертности [14].…”
Section: рисунок 2 -зависимость относительного содержания моноцитов оunclassified